2018
DOI: 10.21873/anticanres.13098
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of GGsTop, Selective Gamma-glutamyl Transpeptidase Inhibitor, on a Mouse Model of 5-Fluorouracil-induced Oral Mucositis

Abstract: Background: Oral mucositis (OM) induced by cancer chemotherapy has a high incidence and serious symptoms, which often force chemotherapy to be stopped. GGsTop is a newly-discovered gamma-glutamyl transpeptidase (GGT) inhibitor. Previous research suggested that inhibition of GGT suppressed reactive oxygen species and induced the production of collagen and elastin. We hypothesized that GGsTop could safely treat OM. Materials and Methods: A mouse model of OM was treated with GGsTop and ulcer area, weight, and whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
1
23
0
3
Order By: Relevance
“…However, most of these compounds have proved to be toxic (20 -22) due to their interference with essential pathways such as the glutamate recycling involved in neurotransmission. Among monophenyl phosphonoglutamate analogues, only the butanoic acid derivative GGsTop was found to be inactive on glutamine amidotransferase (23) and effective for the treatment of oral mucositis (24). In contrast, serine borate was found to be too weak as inhibitor (16,25).…”
mentioning
confidence: 99%
“…However, most of these compounds have proved to be toxic (20 -22) due to their interference with essential pathways such as the glutamate recycling involved in neurotransmission. Among monophenyl phosphonoglutamate analogues, only the butanoic acid derivative GGsTop was found to be inactive on glutamine amidotransferase (23) and effective for the treatment of oral mucositis (24). In contrast, serine borate was found to be too weak as inhibitor (16,25).…”
mentioning
confidence: 99%
“…X‐ray crystallography with Escherichia coli γ‐GT, sequence alignment and site‐directed mutagenesis of human γ‐GT revealed a critical electrostatic interaction between the terminal carboxylate of GGsTop and the active‐site residue Lys562 of human γ‐GT for potent inhibition (Kamiyama et al, 2016). GGsTop promoted collagen production in oral mucosa and has therapeutic effects on oral mucositis (Shimamura, Takeuchi, Terada, & Makino, 2019). It was reported that inhibition of γ‐GT activity in lung lining fluid increased GSH levels and protected lung airway epithelial cells against oxidative stress injury and associated inflammation in a mouse of model of asthma and recommended GGsTop as a novel pharmacological agent for the treatment of asthma (Tuzova et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…GGsTop promoted collagen production in oral mucosa and has therapeutic effects on oral mucositis (Shimamura, Takeuchi, Terada, & Makino, 2019). It was reported that inhibition of γ-GT activity in lung lining fluid increased GSH levels and protected lung airway epithelial cells against oxidative stress injury and associated inflammation in a mouse of model of asthma and recommended GGsTop as a novel pharmacological agent for the treatment of asthma (Tuzova et al, 2014).…”
Section: Treatment With Ggstop Prevented Hepatic Necrosis During Ismentioning
confidence: 99%
“…Glutamine analogues have been developed, acting as irreversible competitive inhibitors due to their binding affinity for the donor site, but most of them have been abandoned in clinical trials due to toxicity [30][31][32]. Glutamic acid/glutamate derivatives have been proven to provide a valid therapeutic alternative, as these irreversible GGT inhibitors are more selective and less toxic [33][34][35][36][37]. Finally, a novel class of uncompetitive inhibitors has also been identified, whose action is displayed by binding to the acceptor site of the enzyme, thus resulting in less toxicity compared to the glutamine analogues [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a butanoic acid derivative (GGsTop) was found to be effective for the treatment of ischemia/reperfusion-induced renal injury, asthma, and oral mucositis [26,27,37]. Moreover, a class of uncompetitive inhibitors, which bind the acceptor site and are less toxic than glutamine analogues, have been developed, but no further in vitro and in vivo studies have confirmed their therapeutic potential [38].…”
Section: Introductionmentioning
confidence: 99%